Prediction of Geraniol Bond Mode in Aspergillus niger Linalool Dehydratase – Isomerase - Yelfi Anwar; Andrianopsyah Mas Jaya Putra; Elvina Dhiaul Iftitah; Partomuan Simanjuntak; Shirly Kumala (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
Geraniol is a very valuable aroma chemical and has commonly been used in fragrances and aroma compound. Geraniol biotransformation by Aspergillus niger has been studied. The main bioconversion products obtained from geraniol and liquid culture of A. niger are linalool and alpha-terpineol. Linalool plays a major role in anti-inflammatory, antibacterial and antioxidant activities. This study aims to know the interaction of geraniol in Aspergillus niger enzyme with docking molecular. Comparative modeling of Aspergillus niger enzyme was conducted by means of one of the crystal structure of Linalool Dehydratase – Idomerase (LDI) as a template. The best model of this comparative modeling was then used in docking molecular to investigate geraniol binding mode inactive site enzyme of Aspergillus niger. Inactive site enzyme of Aspergillus niger, geraniol is located with hydrophobic and hydrogen bonds: Amino acid – the amino acids are Asn 105, Arg 96, Lys 112 inactive site - OH with hydrogen bond, Arg 97 inactive site – CH3 with hydrophobic bond and Leu54 inactive site – CH3 with the hydrophobic bond. The distances among pharmacophore respectively are 3,603 A, 6,768 A, and 7,345A. It has higher score (ΔGbind: -3.4 kcal/mol) compared to linalool (ΔGbind: -3.6 kcal/mol). Virtual tethering of linalool with LDI Aspergillus niger enzyme in amino acid Leu120 and Glu118 had been done. The pharmacophore is - OH and methyl C8 group. The distances among pharmacophore respectively are 5,835 Å, 2,52 Å, and 5,32 Å. Virtual tethering of LDI Aspergillus niger enzyme with geraniol has a higher score (ΔGbind: -3.4 kcal/mol) compared to linalool (ΔGbind: -3.6 kcal/mol). It shows that interaction between linalool and LDI Aspergillus niger enzyme is easier to occur than the interaction between geraniol and LDI Aspergillus niger enzyme, geraniol reaction to linalool that occurs is rearrangement reaction.